Dual-parameter control of the pole frequency in case of universal filter with MCDU elements - Jeřábek, Jan; Šotner, Roman; Herencsár, Norbert; Polák, Josef; Dvořák, Jan; Koton, Jaroslav (Springer, 2016)
This paper presents an universal filter with control of the pole frequency by two mutually independent parameters - current gain (B) and intrinsic resistance (R x) in frame of two modified current differencing unit (MCDU) active elements. This type of control extends and also improves features of the tuning range and is referred to as dual-parameter control. The current-mode filter is of the second order and the required type of the response (low pass, inverting band pass, high pass, band reject and all pass) is obtained by proper selection/combination of input(s) - this filter is of the multiple-input single-output type. The filter employs two capacitors, two MCDUs, each of them with four controllable parameters and one multiple-output current follower. The paper includes tuning range analysis, the simulation results with behavioral models and also laboratory measurement results with the same models. Moreover, designed transistor-level structures of both the active elements proposed in ON Semiconductor I3T CMOS 0.35 um technology that were used for final simulations confirm the workability and features of the designed concept.

This paper presents an universal filter with control of the pole frequency by two mutually independent parameters - current gain (B) and intrinsic resistance (R x) in frame of two modified current differencing unit (MCDU) active elements. This type of control extends and also improves features of the tuning range and is referred to as dual-parameter control. The current-mode filter is of the second order and the required type of the response (low pass, inverting band pass, high pass, band reject and all pass) is obtained by proper selection/combination of input(s) - this filter is of the multiple-input single-output type. The filter employs two capacitors, two MCDUs, each of them with four controllable parameters and one multiple-output current follower. The paper includes tuning range analysis, the simulation results with behavioral models and also laboratory measurement results with the same models. Moreover, designed transistor-level structures of both the active elements proposed in ON Semiconductor I3T CMOS 0.35 um technology that were used for final simulations confirm the workability and features of the designed concept.
Dual-parameter control of the pole frequency in case of universal filter with MCDU elements
Keywords: Current differencing unit; Dual-parameter control; Electronic control; MCDU; Universal filter.; Current differencing unit; Dual-parameter control; Electronic control; MCDU; Universal filter.